Key Genetic Parameters for Population Management - Wellmann, Robin; Bennewitz, Jörn (Frontiers in Genetics, 2019)
Population management has the primary task of maximizing the long-term competitiveness of a breed. Breeds compete with each other for being able to supply consumer demands at low costs, and also for funds from conservation programs. The competition for the consumer preference is won by breeds with high genetic gain for total merit who maintained a sufficiently high genetic diversity, whereas the competition for funds is won by breeds with high conservation value. The conservation value of a breed could be improved by increasing its contribution to the gene pool of the species. This may include the recovery of its original genetic background, and the maintenance of a high genetic diversity at native haplotype segments. The primary objective of a breeding program depends on the genetic state of the population, and its intended usage. In this paper, we review key genetic parameters that are relevant for population management, compare methods for estimating them, derive formulas for predicting their value at a future time, and clarify their usage in various types of breeding programs that differ in their main objectives. These key parameters are kinships, native kinships, breeding values, Mendelian sampling variances, native contributions, and mutational effects. Population management experiences currently a transition from using pedigree-based estimates to marker-based estimates, which improves the accuracies of these estimates and thereby increases response to selection. In addition, improved measures of the factors that determine the competitiveness of a breed and utilize auxiliary parameters such as Mendelian sampling variances, mutational effects and native kinships, enable to improve further upon historic recommendations for genetic population management.